Cyber Crime Classification: Understanding and Categorizing Cybercrime (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As we all know, this is an age in which the majority of activities are done via the internet, fromonline trading to online transactions. Because the internet is seen as a global stage, anybody may use itsresources from anywhere. Few individuals have been utilising internet technology for illegal actions suchas unlawful access to other people's networks, frauds, and so on. Cyber crime refers to these illegalbehaviours or offensescrimes involving the internet. The phrase Computer Law was coined in order todeter or punish cyber thieves.As cybercrime continues to gain notoriety as one of the century's most troubling developments,governments, corporations, and the international community's dedication to combating this epidemic isunsurprising. Combating this ailment, however, will include recognising, diagnosing, and categorisingcybercrime. Meanwhile, the phenomena of cybercrime has become well-known and characterised, withtop-level categorization confined to a duality of computer-assisted and computer-focusedcybercrimes. The categorisation of cybercrime is examined in this paper.